Sesotho Online: establishing an internet-based language knowledge community - Olivier, Jako (Taylor & Francis, 2016)
Online knowledge communities can affect the status of languages within the internet linguistic landscape. Despite the prominence of English in the online environment, multilingualism is increasingly being promoted in these environments. It is against this background that the status, presentation and representation of African languages are being investigated. This article reports on the contribution of the website Sesotho Online to the establishment of an internet-based language knowledge community for the Sesotho language. In its literature review the article considers the concept of language knowledge communities and the internet language landscape with particular reference to Sesotho. Furthermore, an overview of website usage statistics and qualitative research by means of a descriptive study (borrowing from methodologies of autoethnographical enquiry of the author's experiences) is provided. Online trends over the past twenty years are mirrored in the development of the researched website. From reflections on this website, some recommendations are made towards future developments in other African languages, for example. In conclusion, through Sesotho Online, clear lessons are learnt for the development of other internet-based language knowledge communities within the South African and other minority language contexts.